Assessment of health status of home isolated COVID-19 patients in Nepal. - Gyanwali,Pradeep; Dhimal,Meghnath (Nepal Health Research Council., 2020)
Executive Summary: Background The spread of novel coronavirus has resulted in the development of various psychological problems in Nepalese. Patients infected with the disease are also facing stigma and discrimination from their own family, relatives and neighbors, further leading to mental distress such as loneliness, fear, worries, anxiety and depression. This also triggers unhealthy risk behaviors such as smoking, consumption of alcohol, unhealthy eating habits, low physical activity and other lifestyle behaviors. The government of Nepal has recommended home isolation over hospital isolation. So, more than half of the patients with asymptomatic or mild symptomatic cases are at home isolation these days. This study aimed to study the health status of COVID-19 patients staying in home isolation. The findings of this study contribute to understanding the physical and mental wellbeing of COVID-19 patients and their management procedure at home. Method and Materials The study was carried out from the list of home isolated COVID-19 patients available from HEOC and EDCD for asymptomatic cases living in home isolation. A total of 536 COVID-19 home isolated COVID-19 patients were taken. An unstructured questionnaire was designed to be used for a telephonic survey. Home isolated COVID-19 patients covered key issues to elicit their experience as being a COVID-19 patient staying in home isolation in terms of physical, mental and social wellbeing. Results Socio demographic information 1. The majority 310(57.8%) of the participants were male and 226(42.2%) were female. 2. Most 343(64%) of the participants had no travel history, some 102(19%) had travelled between municipalities or rural municipalities followed by 45(8.4%) between provinces, 43(8%) within districts and 3(1%) abroad respectively. 3. 113(21.1%) of participants had co-morbidities (Diabetes, heart disease, lung disease, TB, Asthma, HIV infection) along with COVID- 19 infection. 4. 30(5.6%) were consuming smoking before COVID-19 infection while 16(3%) were consuming smoking during COVID-19 infection. 5. 64(11.9%) were consuming Alcohol before COVID-19 infection whereas 27(4.9%) were consuming alcohol during COVID-19 infection. Physical wellbeing (Current health status) 1. The majority 353(65.9%) of the participants were asymptomatic at the time of the interview. Among the symptomatic cases, the major symptoms were fever, cough, feeling cold weakness, loss of taste, loss of smell, muscle pain, headache, difficulty in breathing, chest pain, sore throat, joint pain and nausea. 2. More than half 313(58.4%) of the participants reported that they felt good followed by the same as usual 187(34.9%) don't know 33(6.2%), and bad 2(0.6%). 3. Most 226(42.2%) of the participants reported very good health followed by good 210(39.2%), normal 76(14.2%), excellent 14(2.6%), bad 7(1.3%) and very bad 1(0.2%). 4. The majority 314(58.6%) of the participants were not doing any work during home isolation, followed by doing all work as before 107(20.0%) and doing normal household work 62(11.6%). Social health (Maintaining social distance and seeking treatment) 1. More than half 281(52.5%) of the participants followed social distance among the family members which is followed by 35 percent of the participants who maintain social distance sometimes only. Likewise, 67(12.5%) participants didn't maintain social distance. 2. The majority 391(72.9%) of the participants seeking treatment for COVID-19. 3. Among the home isolated patients who were seeking treatment for COVID-19, more than half 86(59.3%) of the participants adopted home remedies followed by 43(29.6%) allopathic. Whereas, few 8(5.6%) adopted Ayurveda treatment. Mental health status 1. More than half 312(58.2%) of the participants having some degree of a mental disturbance at some point of time during home isolation. 2. 54(10%) of the participants had very hard to wind down. 3. Few participants 6(1.2%) had mental disturbance at a good point of time. Management of COVID-19 isolated patient 1. 110(20.5%) of the participants were facing difficulties at home isolation. Among them,  47(42.8%) had the problems of a separate room.  29(26.1%) unavailability of a separate toilet bathroom.  22(20.7%) had difficulties in bringing groceries  11(10%) had difficulties in bringing medicines  6(5%) had no family support 2. Majority 514(95.9%) of the participant's family members were taking care of during home isolation. 3. Most of the participants 209(39.1%) adopted home remedies (Turmeric, water, Gurjo) followed by ayurvedic treatment 187(35%) during home isolation Whereas, a few 63(11.7%) adopted allopathic treatment. 4. Majority 406(75.7%) of the participants had access to transportation to a hospital in case of an emergency, whereas, 121(22.6%) had no access to transportation to a hospital in an emergency situation.